1993
DOI: 10.1080/01140671.1993.9513781
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse cultivation of babaco(CaricaxheilborniiBadillo n.m.pentagona(Heilborn)): Effect of media, container size, stem number, and plant density

Abstract: The effects of growing media, pot size, number of stems, and plant density on fruit yields of greenhouse-grown babaco plants (Carica × heilbornii Badillo n.m. pentagona (Heilborn)) were determined. No significant differences were found in the total yield or days to harvest between plants grown in sawdust and Peatlite (2 peat : 1 perlite), nor between plants grown in 23-litre and 45-litre pots, nor between twostemmed and single-stemmed plants. However, twostemmed plants produced significantly more, but smaller,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

1996
1996
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 3 publications
0
9
0
6
Order By: Relevance
“…Après désinfection éventuelle du terrain et ajout de fumure organique, la plantation peut alors être réalisée en double ligne ou en triangle avec une densité de culture de 1 plant pour 1,5 m 2 , soit de (4000 à 6000) plants⋅ha -1 [2,5]. Une densité trop élevée diminue significativement la quantité de fruits produite et peut réduire leur taille jusqu'à 30 % [13].…”
Section: Culture Du Babacounclassified
See 1 more Smart Citation
“…Après désinfection éventuelle du terrain et ajout de fumure organique, la plantation peut alors être réalisée en double ligne ou en triangle avec une densité de culture de 1 plant pour 1,5 m 2 , soit de (4000 à 6000) plants⋅ha -1 [2,5]. Une densité trop élevée diminue significativement la quantité de fruits produite et peut réduire leur taille jusqu'à 30 % [13].…”
Section: Culture Du Babacounclassified
“…En Nouvelle-Zélande les fruits sont récoltés, en général, 11 mois après la plantation. Dans ces pays, malgré une floraison continue sur l'année, la plante ne développe pas de fruits en hivers à cause d'un ensoleillement insuffisant [13,14].…”
Section: Culture Du Babacounclassified
“…Endt (1986) reported that greenhouse cultivation, as opposed to field culture, is necessary to produce high-quality babaco fruit with soft, edible skin. Fortunately, the plants are easily cultivated under greenhouse conditions (Evequoz, 1990;Kempler et al, 1993) (Fig. 2).…”
Section: Importance Origin and Botanymentioning
confidence: 99%
“…The flowering habit of babaco is indeterminate. Under greenhouse conditions, plant growth during the winter months (October-March at 49°N) is slow, and flowers senesce and fail to set fruit (Evequoz, 1990;Kempler et al, 1993). Under field culture in Ecuador, the trees begin cropping 10 months after planting and continue bearing for 6 months, yielding about 40 fruit/tree, each fruit weighing 1 to 1.4 kg (Oosten, 1986).…”
Section: Adaptability and Growing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation